Pengaruh Strategi Bauran Pemasaran terhadap Minat Berkunjung Kembali di Objek Wisata Ruang Terbuka Hijau Taman Hutan Kota Langsa - M. Lutfi Azmi; Tengku Putri Lindung Bulan (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2019)
The purpose of this research was to examine the influence of marketing mix which product, price, promotion, location and physical evidence on revisit intention in Tourist Attractions Ruang Terbuka Hijau Taman Hutan Kota Langsa of students on Fakultas Ekonomi Universitas Samudra. The number of samples in this research as many as 96 respondents. Data analysis method using multiple linear regression analysis. The t test result showed that product, price, location and physical evidence had insignificant influence on revisit intention in Tourist Attractions Ruang Terbuka Hijau Taman Hutan Kota Langsa, while promotion had significant influence on revisit intention. The F test result showed that product, price, location, promotion and physical evidence had significant influence on revisit intention in Tourist Attractions Ruang Terbuka Hijau Taman Hutan Kota Langsa. Based on the results of coefficient of determination can be explained that product, price, promotion, location and physical evidence affect revisit intention in Tourist Attractions Ruang Terbuka Hijau Taman Hutan Kota Langsa by 20,8 %, while the remaining 79,2 % was influenced by other variables not examined in this research such as people and process.